The personal characteristic of younger schoolboys by teachers to be who have different relations with learners - S V Pazukhina (Peoples' Friendship University of Russia (RUDN University), 2010)
Employing the method of personality construction the author of the article reveals the peculiarities of estimation scales, which are used by primary school teachers to be who have formal, positive undifferentiated, cognitive and value types of relations to primary schoolchildren while describing their personality features.